UNDERSTANDING AND SYSTEMATIC APPROACH TO TRACHEOSTOMY: STRATEGIES FOR SUCCESSFUL PROCEDURE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Tracheostomy is an important medical procedure often used in clinical practice to provide access to the airway in patients with various diseases. However, successfully performing this procedure requires not only surgical skill, but also a systematic approach and a thorough understanding of the underlying aspects. This abstract discusses key aspects of tracheostomy, including indications, patient preparation, choice of technique and equipment, procedure performance, postoperative care, and risks and complications. Understanding these aspects is essential to ensure patient safety and successful tracheostomy outcomes.